Early and Severe Dyspnea After Supracricoid Partial Laryngectomy. (January 2014) - Loyo, Myriam; Espinoza, Sophie; Giraud, Philippe; Laccourreye, Ollivier
We present the case of a not-yet-reported complication that occurred during the immediate postoperative period after supracricoid partial laryngectomy. We include a review of the literature on complications following this procedure, emphasizing technical considerations that are critical during this surgery. Clinical, diagnostic, and operative findings are presented, as is a differential diagnosis for early and severe postoperative dyspnea following supracricoid laryngectomy.